2015
DOI: 10.1037/cou0000014
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating an online stress management intervention for college students.

Abstract: The goal of this study was to assess the feasibility and effectiveness of a theory-based online intervention designed to improve stress management in undergraduate students. The intervention focused on present control because it has been found to be associated with a range of positive outcomes, including lower levels of depression, anxiety, and stress, controlling for a range of other variables (e.g., Frazier et al., 2011, 2012). Two pilot studies were first conducted to confirm that our intervention could inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
120
3
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(135 citation statements)
references
References 42 publications
10
120
3
2
Order By: Relevance
“…However, the results of one study [51] were accounted for in one of the other included articles [24] and it was not possible to calculate effect sizes for three studies due to insufficient data [52-54]. In three studies [42,55,56], a small proportion of the participants were younger than 18 years, which was the prespecified criterion of being classified as adults. Because the studies fit all the other inclusion criteria and our sensitivity analyses indicated no difference in the overall results, we decided to include those studies.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…However, the results of one study [51] were accounted for in one of the other included articles [24] and it was not possible to calculate effect sizes for three studies due to insufficient data [52-54]. In three studies [42,55,56], a small proportion of the participants were younger than 18 years, which was the prespecified criterion of being classified as adults. Because the studies fit all the other inclusion criteria and our sensitivity analyses indicated no difference in the overall results, we decided to include those studies.…”
Section: Resultsmentioning
confidence: 99%
“…Selected characteristics of the 23 included studies [21-39,42,55-57] are presented in Table 1 (trial characteristics) and Table 2 (intervention characteristics). A more detailed description of the interventions is available in the Multimedia Appendix 2.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…An evidence-based online present control intervention (Hintz, Frazier & Meredith, 2015) is being adapted for this patient population.…”
Section: Discussionmentioning
confidence: 99%